2019
DOI: 10.5267/j.msl.2019.7.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of accounting disclosures on individual investors’ decision making in Vietnam Stock Market

Abstract: This paper presents an empirical investigation on the perceptions of individual investors about the impact of accounting disclosures on their decision makings on the stock exchange market. The study uses some quantitative methods with survey questionnaires sent to investors participating in the Vietnam stock market. By using SPSS 22, the research develops a research model with 11 accounting information groups (factors) which are measured by 82 items. The results indicate that the income information significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similarly, Al-Malkawi et al ( 2018) found that book value per share, dividend per share, earnings per share, return on equity, and price-earnings ratio positively affect market share price whereas the size of the company poses a statistically significant impact on the market share price of the 277 companies listed in the Middle East and North Africa regions. Dang and Tran (2018) explained that cash flow from operating activities, earnings per share, firm size, and book value are noticed to have a positive association with the market share price of Vietnam Stock Exchange-listed companies. These four factors have a combined influence of 48.1% on the share price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Al-Malkawi et al ( 2018) found that book value per share, dividend per share, earnings per share, return on equity, and price-earnings ratio positively affect market share price whereas the size of the company poses a statistically significant impact on the market share price of the 277 companies listed in the Middle East and North Africa regions. Dang and Tran (2018) explained that cash flow from operating activities, earnings per share, firm size, and book value are noticed to have a positive association with the market share price of Vietnam Stock Exchange-listed companies. These four factors have a combined influence of 48.1% on the share price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women entrepreneurs' investment decisions have become more difficult due to the prevalence of irrational behavior in recent decades (Iram, Bilal, Ahmad & Latif, 2022a: Salim & Khan, 2020. Many investors are particularly concerned about their investment decisions since every entrepreneur expects to earn more profits, based on their decisions (Dang et al, 2019;and Ghaeli, 2019). In this regard, Salim (2015) argues that a wide range of benefits is enclosed within rational investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…A survey undertaken by Amahalu et al (2020) stated that a financial statement is one of the essential statements required in deciding on an investment, especially in the private sector. Neogy and Ahmed (2015), Ahmed et al (2011), andDang et al (2019) stated that the disclosed accounting information has a tangible impact on the process of decision-making of users, especially investors. Financial reporting means preparing and publishing the financial statements and related information by the business enterprise to the interested parties.…”
Section: Introductionmentioning
confidence: 99%